2013
DOI: 10.1080/15287394.2013.792024
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary and Cardiovascular Responses of Rats to Inhalation of Silver Nanoparticles

Abstract: Exposure to wet aerosols generated during use of spray products containing silver (Ag) has not been evaluated. The goal was to assess the potential for cardiopulmonary toxicity following an acute inhalation of wet silver colloid. Rats were exposed by inhalation to a low concentration (100 μg/m(3) ) using an undiluted commercial antimicrobial product (20 mg/L total silver; approximately 33 nm mean aerodynamic diameter [MAD]) or to a higher concentration (1000 μg/m(3)) using a suspension (200 mg/L total silver; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 36 publications
1
37
1
Order By: Relevance
“…Of interest, there appears to minimal inflammation in the lung in terms of gross histologic morphology, cell differentials and bronchoalveolar lavage protein, conforming the reports from other studies that do not report acute overt lung toxicity following exposure to AgNPs [10,23,34,35]. However, we report an increase in serum cytokine concentrations and cardiac injury following exposure to AgNP.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Of interest, there appears to minimal inflammation in the lung in terms of gross histologic morphology, cell differentials and bronchoalveolar lavage protein, conforming the reports from other studies that do not report acute overt lung toxicity following exposure to AgNPs [10,23,34,35]. However, we report an increase in serum cytokine concentrations and cardiac injury following exposure to AgNP.…”
Section: Discussionsupporting
confidence: 90%
“…In metal derived nanomaterials [8] and the interactions of ENM in vivo , nanoparticle size and chemical composition may be an important factor in determining toxicological impact of AgNP exposure. Surface oxidation of AgNP may lead to oxidative stress and interactions with macromolecules that alter signaling processes, contributing to cardiovascular dysfunction following pulmonary exposure to AgNP [9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…The energy and water consumed to manufacture, transport, and include the nanomaterials into the paint formulation will vary depending upon precursor nanomaterial manufacturing process selected, and the final viscosity of the paint; however, the calculation of these totals will ultimately be used to compare against the sustainability performance target to evaluate if the solution increases overall sustainability, relating to the variable X 7 , through measurement of the gallons of paint used and multiplying by the marginal energy costs. For example, it is reported in literature synthesis approaches to achieve AgNPs on the order of mg/L, which are then purified and concentrated up to mg/mL [9,27,35]. The resulting waste stream from this concentration and purification must often be treated as hazardous waste, due to the risk of it containing traces of dissolved silver or AgNPs.…”
Section: Comparison Of Biocidal Paint To Normal Paintmentioning
confidence: 99%
“…It was observed that after a short time of inhalation, silver nanoparticles did not cause significant changes in the studied parameters and only increased heart rate values were observed. However, the accumulation of silver nanoparticles in the bodies of rats was confirmed [107].…”
Section: The Impact Of Silver Nanoparticles On Living Organismsmentioning
confidence: 99%